CORROSION BEHAVIOR OF Zr-10Mo ALLOYS IN NIOBIUM-DOPED LACTATE RINGER’S SOLUTION - Vita Yuliana Prastika; Pradoto Ambardi; Djoko Hadi Prajitno (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2019)
This research discusses the corrosion behavior of Zr-10Mo alloys in Niobium-doped lactate ringer ’s solution. The addition of Niobium of 1%, 3% and 5% on Zr-10Mo alloys aims to study the effect of adding Niobium to the hardness, microstructure and corrosion resistance of Zr-Mo alloys. The alloys are made by melting the materials of Zr, Mo and Nb with a certain percentage of weight using single arc melting furnace in Argon atmosphere with high purity and Tungsten eletrodes. The alloys (as cast) are subjected to hardness testing using C-scale rockwell, microstructure using optical microscopy, compounds and phases in the alloys (as cast) using XRD and corrosion testing using polarization method in lactate ringers’ solution. The hardness value increases by the addition of Niobium, Zr-10Mo-1Nb alloy of 34 HRC, Zr-10Mo-3Nb alloy of 38 HRC and Zr-10Mo-5Nb alloy of 41.5 HRC. The basketweave-shaped microstructure with the addition of Niobium creates relatively smaller grain size. The value of corrosion rate decrases by the addition of Niobium at the immersion times of 0 minute, 60 minutes and 120 minutes, Zr-10Mo-1Nb alloy of 4.208 mpy, Zr-10Mo-3Nb alloy of 3.538 mpy and Zr-10Mo-5Nb alloy of 2.813 mpy, included in the excellent category (1-5 mpy).